2020
DOI: 10.2196/19276
|View full text |Cite
|
Sign up to set email alerts
|

Mining Physicians’ Opinions on Social Media to Obtain Insights Into COVID-19: Mixed Methods Analysis

Abstract: Background The coronavirus disease (COVID-19) pandemic is considered to be the most daunting public health challenge in decades. With no effective treatments and with time needed to develop a vaccine, alternative approaches are being used to control this pandemic. Objective The objective of this paper was to identify topics, opinions, and recommendations about the COVID-19 pandemic discussed by medical professionals on the Twitter social medial platform… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 21 publications
2
70
1
2
Order By: Relevance
“…Our study extends similar findings from a previous study conducted in the United States, which found general health information online was positively related to preventive behavior [ 34 ]. Our findings indicate the potential roles of social media and traditional media to deliver effective preventive campaigns related to COVID-19 [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 90%
“…Our study extends similar findings from a previous study conducted in the United States, which found general health information online was positively related to preventive behavior [ 34 ]. Our findings indicate the potential roles of social media and traditional media to deliver effective preventive campaigns related to COVID-19 [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 90%
“…Waiting for the development and rollout of a vaccine, governments across the world have implemented wide-ranging nonpharmaceutical interventions such as hand hygiene, face masks, contact tracing, isolation and quarantine, and physical (social) distancing through banning mass gatherings and lockdowns to reduce the transmission of SARS-CoV-2. The impact of COVID-19 and measures to prevent transmission has generated a lot of discussion among the general population, medical and public health professionals, and government officials [ 2 , 3 ]. Some of this discourse is happening on social media such as Twitter.…”
Section: Introductionmentioning
confidence: 99%
“…An extensive range of tweets has been shared by users and the general public, although politicians (Rufai & Bunce, 2020;Yum, 2020), physicians, and health professionals (Kudchadkar & Carroll, 2020;Wahbeh et al, 2020) have also utilized this platform to share news and provide information to people. Regular users on Twitter share most of their opinions, experiences, and feelings about the crisis.…”
Section: Discussionmentioning
confidence: 99%
“…Self-reported COVID-19 symptoms on Twitter: an analysis and a research resource (Sarker et al, 2020) -Users have expressed their symptoms and described the progress of the disease by tweeting on Twitter (Wahbeh et al, 2020) -Classification of physicians' and health professionals' tweets regarding the topics of measures and recommendations, coping with false information and the capacity of the health care system to handle the COVID-19 epidemic, information, and knowledge, symptoms and disease, immunity, and safety of people against the coronavirus, tests related to COVID-19, infection, and transmission Retweeting COVID-19 disability issues: Risks, support, and outrage (Thelwall & Levitt, 2020) Tweets related to people with certain conditions are categorized as follows: -Support for people with disabilities against this disease -Lack of attention to people with physical disabilities -Most people with disabilities are at risk -Reports on the death of people with disabilities due to COVID-19 as a warning -Principles of care for people with disabilities -The skills of people with disabilities to use communication technologies -Other problems related to people with disabilities and COVID-19…”
Section: Topics Discussed In the Tweetsmentioning
confidence: 99%